BEYOND TQM: LEVERAGING QUALITY MANAGEMENT PRACTICES FOR ENHANCED PERFORMANCE AND SUSTAINABILITY IN SURABAYA UNIVERSITIES - Audrey, Evelyn; Sutrisno , Timotius F. C. W. (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
This study investigates the impact of quality management (QM) practices on organizational performance and innovation in higher education institutions (HEIs), which face increasing challenges from global competition, technological changes, and funding pressures. While QM practices have been extensively studied in manufacturing and service sectors, their application in HEIs remains underexplored, particularly in terms of distinguishing between soft (human-centered) and hard (technical) practices. This research addresses that gap by adopting a multidimensional perspective to examine how both soft and hard QM practices influence organizational performance and sustainability. The findings show that balancing soft QM elements, such as top management support, student focus, supplier management, people management, strategic planning, with hard QM processes, like process management, information and analysis, continuous improvement, and program design are critical to improving performance and fostering sustainability in HEIs.